Compulsory Voting, Voter Turnout and Asymmetrical Habit-formation - Stefanie Gäbler; Niklas Potrafke; Felix Rösel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We examine whether compulsory voting (CV) influences habit-formation in voting asymmetrically across parties. We use a Differences-in-Differences and a Differences-in-Discontinuity approach to investigate the long-term effects of CV on turnout and party vote shares in Austria. The results show that CV increased turnout. When CV was abolished, turnout returned to the pre-compulsory level. We conclude that CV was not habit-forming and may have crowded out intrinsic motivation.
Keywords: D72; P16; 330